Republication of “Principles of effective course design: What I wish I had known about learning-centered teaching 30 years ago” - Whetten, David A. (Journal of management education, 2021)
Ten years ago, after 20 years as a university professor, I was asked to direct the teaching and learning support center at my university. I quickly realized I had almost no knowledge of the published scholarship on this subject. From my reading of this literature, I found the research on the predictors of student learning particularly informative. In particular, I gained an appreciation for the impact of course design. In this article, I summarize a framework for designing “significant learning experiences.” In discussing the three key components of course design (learning outcomes, learning activities, and learning assessments), I offer tips and give examples relevant for the field of management. My intent is to share the most important information I have learned from a decade of conversations with experts on student learning—the things I wish someone had taught me 30 years ago.